Dissecting the mechanisms of linezolid resistance in a drosophila melanogaster infection model of staphylococcus aureus (2013)
Background. Mini-host models are simple experimental systems to study host-pathogen interactions. We adapted a Drosophila melanogaster infection model to evaluate the in vivo effect of different mechanisms of linezolid (LNZ) resistance in Staphylococcus aureus. Methods. Fly survival was evaluated after infection with LNZ-resistant S. aureus strains NRS119 (which has mutations in 23S ribosomal RNA [rRNA]), CM-05 and 004-737X (which carry cfr), LNZ-susceptible derivatives of CM-05 and 004-737X (which lack cfr), and ATCC 29213 (an LNZ-susceptible control). Flies were then fed food mixed with LNZ (concentration, 15–500 µg/mL). Results were compared to those in mouse peritonitis, using LNZ via oral gavage at 80 and 120 mg/kg every 12 hours. Results. LNZ at 500 µg/mL in fly food protected against all strains, while concentrations of 15–250 µg/mL failed to protect against NRS119 (survival, 1.6%–20%). An in vivo effect of cfr was only detected at concentrations of 30 and 15 µg/mL. In the mouse peritonitis model, LNZ (at doses that mimic human pharmacokinetics) protected mice from challenge with the cfr+ 004-737X strain but was ineffective against the NRS119 strain, which carried 23S rRNA mutations. Conclusions. The fly model offers promising advantages to dissect the in vivo effect of LNZ resistance in S. aureus, and findings from this model appear to be concordant with those from the mouse peritonitis model